Molecular characterization of bovine tuberculosis strains in two slaughterhouses in Morocco - Hind Yahyaoui-Azami; Hamid Aboukhassib; Mohammed Bouslikhane; Jaouad Berrada; Soukaina Rami; Miriam Reinhard; Sebastien Gagneux; Julia Feldmann; Sonia Borrell; Jakob Zinsstag (BMC Veterinary Research, 2017)
Abstract Background Bovine tuberculosis (BTB) is caused by Mycobacterium bovis, which belongs to the Mycobacterium tuberculosis complex. Mycobacterium bovis have been described to be responsible of most cases of bovine tuberculosis. Although M. tuberculosis, M. africanum and non-complex mycobacteria were isolated from cattle. In Morocco, so far, no molecular studies were conducted to characterize the strains responsible of BTB. The present study aims to characterize M. bovis in Morocco. The present study was conducted in slaughterhouses in Rabat and El Jadida. Samples were collected from 327 slaughtered animals with visible lesions suggesting BTB. Results A total of 225 isolates yielded cultures, 95% (n = 215) of them were acid-fast (AF). Sixty eight per cent of the AF positive samples were confirmed as tuberculous mycobacteria (n = 147), 99% of these (n = 146) having RD9 and among the latter, 98% (n = 143) positive while 2% (n = 3) negative for RD4 A total of 134 samples were analyzed by spoligotyping of which 14 were in cluster and with 41 different spoligotypes, ten of them were new patterns (23%). The most prevalent spoligotypes were SB0121, SB0265, and SB0120, and were already identified in many other countries, such as Algeria, Spain, Tunisia, the United States and Argentina. Conclusion The shared borders between Algeria and Morocco, in addition to the previous importation of cattle from Europe and the US could explain the similarities found in M. bovis spoligotypes. On the other hand, the desert of Morocco could be considered as an efficient barrier preventing the introduction of BTB to Morocco from West Central and East Africa. Our findings suggest a low level endemic transmission of BTB similar to other African countries. However, more research is needed for further knowledge about the transmission patterns of BTB in Morocco.